Experimental investigation of shale oil recovery from Qianjiang core samples by the CO2 huff-n-puff EOR method. Issue 49 (13th September 2019) - Li, Lei; Wang, Chengwei; Li, Dongsheng; Fu, Jingang; Su, Yuliang; Lv, Yuting
Abstract : The shale oil recovery potential through the CO2 HnP method on cores with/without fractures was evaluated. Abstract : CO2 Huff-n-Puff (HnP) is an effective technique for enhancing oil recovery (EOR) that can be applied to shale oil reservoirs faced with poor natural productivity and low water injectivity. The main objective of this study is to investigate the interactions of CO2 and formation crude oil, and evaluate the CO2 HnP performance in shale oil reservoirs in the Qianjiang depression in China. In this study, the variation rules of oil phase behavior, viscosity, saturation pressure, and swelling factor at different CO2 contents of 0 to 65% were studied. A series of HnP experiments were conducted. The factors affecting the oil recovery were discussed, and Nuclear Magnetic Resonance (NMR) tests were conducted on core samples at different stages of the HnP process. The results show that the injected CO2 can make an positive change in the crude oil phase behavior. The oil–gas two-phase region enlarges and the saturation pressure increases as more CO2 is dissolved in the formation oil, which is beneficial to oil production. The dissolution of CO2 in the oil phase increased the oil swelling degree by 1.492 times, and the viscosity decreased from 1.944 to 0.453 mPa s. The HnP experimental results demonstrate that the soaking time should be determined based on the injection pressure. Miscible conditions is a viable option for CO2 HnP as 10% more oil can be produced using miscible HnP and save more than half of the soaking time. The results illustrate that fracture is the most important factor affecting oil recovery, and the performance of HnP EOR on core samples with fractures is almost 25% better than those without fractures. However, the core matrix permeability has an almost negligible effect on the performance of CO2 HnP. The NMR tests show that the oil recovered in the first cycle was dominated by macropores and mesopores, followed by small pores. In the latter HnP cycles, the oil in small pores and micropores becomes the main oil-producing area. This study may provide a better understanding of the CO2 HnP enhanced recovery strategy for shale reservoirs.